The Effectiveness of Supportive Educative in Increasing Self Regulation, Self Efficacy, and Self Care Agency to Control Glichemic Index in Patient with Type II Diabetes - Darmansyah AF; Nursalam Nursalam; Suharto Suharto (Jurnal Ners, 2013)
Introduction: Type 2 Diabetes Mellitus (DM) is a chronic disease that requires long-term treatment. Supportive educative model facilitates self care agency improvement through self regulation and self effi cacy. This study was aimed the impact of supportive educative model on the improvement of self care regulation and self effi cacy on an increased of self care agency as well as HbA1c.Method: The research method used was quasy experimental with pre-post control group design. This study was conducted with a sample size of 76 patients with Diabetes Mellitus type 2 who were selected through consecutive sampling, they were divided into treatment group of 38 subjects and control of group 38 subjects. Data were collected by questionnaire and HbA1c test. Analysis of the data used paired t-test, independent t test and Partial Least Square (PLS).Result: Result showed that Supportive Educative Model affect on self regulation on dietary control and diet, physical exercise, medication, blood sugar control and foot care (p = <0.05), self efficacy (p = 0,05), self care agency (p = <0,05). Test result of the correlation among the variables using Partial Least Square (PLS) suggest supportive educative model and the obtained value of self regulation is (0,561), self effi cacy is (0,548) self regulation to self care agency (0,592), self effi cacy to self regulation (0,162), self regulation to self care agency (0,094), and self care agency to HbA1c (0,130). Discussion and Conclusion: Novelty in this study indicated that supportive educative is able to improve self care agency patient and HbA1c through increasing self regulation. It is recommended that model of supportive educative could be applied in health service in Indonesia in regard to be independency patient with type 2 DM and other chronical disease.